Co-operative business: It’s ability to meet customer satisfaction / Norudin Mansor and Ahmad Syazli Abd Halim - Mansor, Norudin; Abd Halim, Ahmad Syazli (2004)
The primary purpose of this article is to clarify the performance of co-operative business as measured by satisfaction level among the customer towards the services rendered by the co-operative business. Co-operative businesses are always been accepted as one of the platform for the Malaysian to invest and to increase their economics well being and to be among the players in developing the economy. It is very much relevant to undertake the investigation so as to ensure that co-operative business will sustain its competitiveness and successfully operates in the globalize economy. Drawing on the findings from the selected unit of analysis, namely the younger generation such as students from higher institution learning, we suggest that there are several independent effect such as, product offered and the layout of the product line provides a strong influence on the performance of the business. Meanwhile the handling of the services and time allocated to deal with the consumer indicated substantial effort needed to be improved if the businesses are expected to deliver their best performance